Exploring the potential of Facebook group discussion platform for trainee teachers’ reflective practice - Ariffin, Natasha; Razali, Abu Bakar (Human Resource Management Academic Research Society, 2019)
The teacher training institution is an important place in supplying content and pedagogical training to teacher trainees. However, applying this knowledge in a natural setting is another challenge faced by the trainee teachers. Thus, there is a need to empower the capability of trainee teachers to refine their teaching skills independently. One of the ways to develop and cultivate this need is by improving how reflective practice is conducted during their teacher practice. The issue of improving the quality of reflective practice has been addressed especially through variety of mediums, such as the use of paper-based method and electronic-based method, and such as the use of blog sites, online forums and chat sites, and more recently social networking sites, like Facebook. However, the use of social networking websites, such as Facebook, have received little attention, even though a handful of studies have reported on its many benefits for reflective practice. Therefore, this conceptual paper is written to provide a review of past studies that explored the potential of using Facebook Group discussion platform for trainee teachers as a tool for reflective practice.